THE PROFILE OF INDONESIAN EFL TEACHERS’ READING ENGAGEMENT VIEWED FROM BEHAVIORAL, AFFECTIVE, COGNITIVE, AND SOCIAL DIMENSIONS - Muniroh, Siti; Karmina, Sari; Widiati, Utami; Nurlaila; Silfia, Dian Indah (TEFLIN Journal, 2024)
This study describes Indonesian secondary school EFL teachers’ and students’ profiles of reading engagement, which comprises behavioral, affective, cognitive, and social dimensions. The researchers employed a survey design involving 70 teachers and 828 students of secondary schools in 50 regions in Java, Sumatra, and the Borneo Islands. The instrument used was a teacher questionnaire and a student questionnaire which contained 16 close-ended questions and 7 open-ended questions. The data from close-ended responses were tabulated and presented in percentages, while the data from open-ended responses were analyzed based on themes, then shown in excerpts. The key findings reveal that four dimensions of reading engagement have been implemented by EFL teachers. Both students and teachers show positive reading behavior and attitude toward reading materials and activities. These findings map the reading engagement practiced in EFL classes in secondary schools in Indonesia, which add knowledge about RE strategies improving EFL teachers’ strategies to engage students in reading English texts, which is expected to enhance students’ English reading comprehension and literacy.